'Patchiness' and basic cancer research: unravelling the proteases. Issue 15 (3rd August 2019) - Soond, Surinder M; Kozhevnikova, Maria V; Zamyatnin Jr, Andrey A
ABSTRACT: The recent developments in Cathepsin protease research have unveiled a number of key observations which are fundamental to further our understanding of normal cellular homeostasis and disease. By far, the most interesting and promising area of Cathepsin biology stems from how these proteins are linked to the fate of living cells through the phenomenon of Lysosomal Leakage and Lysosomal Membrane Permeabilisation. While extracellular Cathepsins are generally believed to be of central importance in tumour progression, through their ability to modulate the architecture of the Extracellular Matrix, intracellular Cathepsins have been established as being of extreme significance in mediating cell death through Apoptosis. With these two juxtaposed key research areas in mind, the focus of this review highlights recent advancements in how this fast-paced area of Cathepsin research has recently evolved in the context of their mechanistic regulation in cancer research. Abbreviations : ECM, Extracellular Matrix; MMP, Matrix Metalloproteases; LL, Lysosomal Leakage; LMP, Lysosomal Membrane Permeabilisation; LMA, Lysosomorphic Agents; BC, Breast Cancer; ASM, Acid Sphingomyelinase; TNF-α, Tumor Necrosis Factor-alpha; LAMP, Lysosomal Associated membrane Protein; PCD, Programmed Cell Death; PDAC, Pancreatic Ductal Adenocarcinoma; ROS, Reactive Oxygen Species; aa, amino acids.